Long-haul dual-channel bidirectional chaos communication based on polarization-resolved chaos synchronization between twin 1550 nM VCSELs subject to variable-polarization optical injection - Wang, Ling; Wu, Zheng-Mao; Wu, Jia-Gui; Xia, Guang-Qiong (Optics communications, 2015)
Based on the polarization-resolved chaos synchronization between twin 1550nm vertical-cavity surface-emitting lasers (VCSELs), a novel long-haul dual-channel bidirectional chaos communication system is proposed. In this system, a time delay signature (TDS)-suppressed chaotic signal, generated by a driving VCSEL (D-VCSEL) under double external cavity feedbacks (DECFs), simultaneously injects into twin VCSELs by variable-polarization optical injection (VPOI) to synchronize them and enhance the chaos output bandwidth of the two VCSELs. The simulated results show that, under proper injection parameters, high-quality polarization-resolved chaos synchronization between the twin VCSELs can be achieved; meanwhile the bandwidths of chaotic signals output from the twin VCSELs have been enhanced in comparison with that of the driven chaotic signal. Based on the high-quality polarization-resolved chaos synchronization, after adopting polarization-division-multiplexing (PDM) and chaos masking (CM) techniques, four 10Gb/s messages hidden respectively in four chaotic carriers can be decrypted effectively after propagating 15km in single-mode fiber (SMF) links. After adopting dispersion-shifted fibers (DSFs) as fiber links, the dual-channel bidirectional chaos communication distance can be extended to 140km.